Estrogen-Related Receptor-γ Regulates Estrogen Receptor-α Responsiveness in Uterine Endometrial Cancer. Issue 9 (1st November 2012) - Yamamoto, Takuro; Mori, Taisuke; Sawada, Morio; Kuroboshi, Haruo; Tatsumi, Hiroshi; Yoshioka, Takashi; Matsushima, Hiroshi; Iwasaku, Kazuhiro; Kitawaki, Jo
Abstract : Objective: Estrogen-related receptors (ERRs) are orphan nuclear receptors that modulate the estrogen receptor (ER)-mediated pathway and play roles in the regulation of breast and prostate cancer cell growth. However, the significance of the localization and the function of ERRs in uterine endometrial cancer remain unclear. We aimed to measure the expression of ERRγ and determine its association with the ER-mediated pathway in human endometrial cancer. Methods: Proliferation, luciferase, and quantitative polymerase chain reaction assays were performed in ERα-positive (Ishikawa) and ERα-negative (HEC1A) endometrial cancer cell lines. The association between ERRγ and ERα expressions was determined by immunohistochemical analysis in uterine endometrial cancer tissues. Results: Estrogen-induced estrogen response element transcriptional activity was repressed by ERRγ in ERα-positive cells but was stimulated by ERRγ in ERα-negative cells. The stable overexpression of ERRγ regulated the in vitro cell growth in the ERα-positive and ERα-negative endometrial cancer cell lines. A selective ERRγ agonist, DY131, inhibited the growth of the ERα-positive endometrial cancer cells but promoted that of the ERα-negative cancer cells. Furthermore, we found that ERRγ is expressed in the nuclei of human uterine endometrial cancer tissues. Estrogen-related receptor γ was not associated with pathological parameters such as the International Federation of Gynecology and Obstetrics stage and histological type. The uterine endometrial cancer tissues with ERRγ-positive/ERα-negative status may have a significantly poor prognosis. Conclusions: The relationship between ERRγ and ERα status could be a predictive marker for the treatment of uterine endometrial cancer, which provides an impetus for the identification of ligands for nuclear orphan receptor ERRγ.